Gradual Goals of Energy Transformation and Upgrading in China’s Power Industry Considering Production Profiles - Lu, Gang; Yan, Xiaoqing; Duan, Na (Frontiers in Energy Research, 2021)
As the largest processing sector of primary energy, the transformation and upgrading of the power sector is undoubtedly an effective way to alleviate the situation of energy and environment. This paper studies the gradual goals of the transformation and upgrading of China’s power industry, where the conditions of technical judgment, specific profile, and moderate agenda are incorporated. The empirical analysis of China’s provincial power sectors based on the constructed models came to the following results. First, it is of great importance to consider the profile of each region’s power sector in setting energy-saving and emission reduction targets. The analysis of variance demonstrates significant differences in the reference points of inputs and outputs under the 1% confidence level. Second, regardless of the specific quantity, the strongly consistent trends of the short- and long-term targets demonstrated the feasibility and effectiveness of the gradual goals. Finally, realizing the potential of energy-saving and emission reduction needs a gradual pathway instead of accomplishing in one stroke. The targets of this study which are attainable for the power sector and still represent best practice, could serve as transitional benchmarks in power supply and emission reduction. To further achieve carbon neutrality, it needs to transform the management strategy to coordinate power supply and renewable energy accommodation.